Interest Rate and Economic Growth as Determinants of Firm’s Investment Decision in Nigeria: A Cointegration Approach: Array - Olaniyan, Niyi Oladipo; Adegboyo, Olufemi Samuel; Olumuyiwa, Owoniya Babajide; Abidemi, Alaketu Akeem (EuroEconomica, 2020)
The study examined the impact of interest rate and economic growth as determinant of the firm’s investment decision in Nigeria between the period of 1989 and 2019. The study disaggregated interest rate and economic growth into external borrowing, exchange rate, inflation rate, and gross domestic product in line with the predicated theories reviewed. The data were obtained from the Central Bank of Nigeria Statistical Bulletin. Based on the mixed level of stationarity of the variables as revealed by the unit root test, the study made use of the auto-regressive distributed lag (ARDL) technique to analyze the data. The bound test revealed that; there was the presence of co-integration (long-run relationship) among the dependent and all the explanatory variables consequently the study estimated the ARDLECM. The findings from the result point to a unique long-term relationship between interest rates, external borrowing, exchange rate, and economic growth. The result also revealed that there is no strong empirical evidence that there is a link between the interest rate and investment decisions in Nigeria. It was concluded that as a prerequisite for economic growth, the government must embark on growth-enhancing reforms and be tender to the behavior of interest rates in the economy. This will guide the formulation of private sector development policy as an enabler of global economic growth in Nigeria.